Lt. General Russel Honore Event Poster - Kansas State University, K-State First (Kansas State University. K-State First., 2011)
An advertisement for the visit of Lieutenant General Russel HonorÃ© when he visited Kansas State University in 2011. Lt. Gen. HonorÃ© was the Commander of Joint Task Force Katrina, and retired after 37 years of active service in the United States Army.
Keywords: Hurricane Katrina; First-year experience program; Common reading program; Engagement; Events; Zeitoun; Promotional materials